2019
DOI: 10.29312/remexca.v10i1.1211
|View full text |Cite
|
Sign up to set email alerts
|

Densidad de plantas y poda de tallos en la producción de pepino en invernadero

Abstract: La densidad de plantas o tallos es una variable de manejo agronómico asociada a la productividad de hortalizas bajo condiciones protegidas. La investigación se realizó con el objetivo de conocer la influencia de la densidad de plantas y poda de tallos sobre el crecimiento de planta y rendimiento de frutos de pepino cultivado bajo condiciones de invernadero. Se usó el diseño de bloques completos al azar en arreglo factorial, con dos niveles cada factor: densidad de plantas (1.68 y 2.22 plantas/m2) y poda de tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
3
9
0
1
Order By: Relevance
“…There were no significant differences between the treatments (p0.05) with respect to stem diameter. The results in this research were on average of 1.1 cm, which agree with those reported by Ayala-Tafoya et al (2019) who found a stem diameter of 1.07 cm in cucumber plants "Alanis RZ F1" variety planted at a density of 1.68 plants m 2 and pruned to one stem per plant. Gabriel-Ortega et al (2022) reported a 0.98 cm stem diameter in the variety "Intimator".…”
Section: Stem Diameter and Number Of Leavessupporting
confidence: 92%
See 2 more Smart Citations
“…There were no significant differences between the treatments (p0.05) with respect to stem diameter. The results in this research were on average of 1.1 cm, which agree with those reported by Ayala-Tafoya et al (2019) who found a stem diameter of 1.07 cm in cucumber plants "Alanis RZ F1" variety planted at a density of 1.68 plants m 2 and pruned to one stem per plant. Gabriel-Ortega et al (2022) reported a 0.98 cm stem diameter in the variety "Intimator".…”
Section: Stem Diameter and Number Of Leavessupporting
confidence: 92%
“…33 leaves per plant were obtained in the three treatments and 31 leaves in the control, with no significant differences due to application of phytohormones. Ayala-Tafoya et al (2019) reported 41 total leaves and 260 cm height in a cucumber crop grown in a greenhouse. The number of leaves is directly related to the leaf area.…”
Section: Stem Diameter and Number Of Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem pruning and plant spacing are essential practices in maximizing plant production area and improving yield and quality of tomato (Ara et al, 2007). Previous studies have also established linear increase in fruit yield in pepper and cucumber with increasing plant density and stem pruning (Nasto et al, 2009;Maboko et al, 2011;Amundson, 2012;Maboko et al, 2012;Ayala-Tafoya et al, 2019). Plant yield and economic returns, especially with fruiting vegetables can, therefore, be potentially improved in aquaponic operations with the adoption of best cultural practices.…”
Section: Plants Production In Aquaponicsmentioning
confidence: 93%
“…Jovicich et al (1999) reported similar findings with sweet pepper with a plant density of 4 plants /m 2 pruned to four stems and Maboko et al (2011) with a tomato plant density of 3 plants /m 2 pruned to two stems. The optimum plant density per square meter is largely dependent on many factors such as the genotype, plant management practices and environmental conditions Ayala-Tafoya et al (2019). Higher productivity of plants with increasing density is due to greater capture sunlight and increasing photosynthetic activities resulting in plant growth and fruit production Peil and de Albuquerque Neto (2014).…”
Section: Yield Of Tomato Due To Plant Density and Stem Pruningmentioning
confidence: 99%